Etos Kerja Pedagang Tradisional di Tengah Maraknya Pasar Modern (Studi Deskriptif Pada Pedagang Pasar Tradisional "Pajak Sore" Padang Bulan, Medan) - Ninda Ovtika Sinaga (Perspektif Sosiologi, 2012)
ABSTRACT Nowadays, modern market is more much than of traditional market, and it make both have competition. Retail company, such Hypermarket, Carefour, and Indomaret, lately grow up more faster making competition have impact to traditional merchant. Traditional merchant must performing they role better on this condition, so that  traditional market in Indonesian especially Medan city can be survive. Merchant traditional have important role to advance trading activity in traditional market with notice they work ethic.                                      Location this research in traditional market Padang Bulan, Medan. this location selected because location close with many modern market, so it make researcher can seen the extent to which trading activity is running.   Keyword: work ethic, traditional market, traditional merchant.